Awareness about COVID-19 among Patients Attending the Out-patient Department of a Tertiary Dental Care Center: A Cross-Sectional Study - Dhanya Shaji; Subija Kunnumpurath Narayanankutty; Jinu George; Divia Attuvalappil Rajan; Christalin Ramakrishnan; Shalmiya Karukappadath Ibrahim (Wolters Kluwer Medknow Publications, 2024)
Objective: The study aimed to assess coronavirus disease 2019 (COVID-19) knowledge among dental patients seeking treatment at a tertiary care center. Materials and Methods: A cross-sectional study was conducted at the Government Dental College Thrissur to assess dental patients' COVID-19 awareness. Patients over 18 who attended the dental department and agreed to participate were included after obtaining the informed consent. A validated self-administered questionnaire study was done. Results: The sample had an average age of 39.68 ± 13.83 years. The study included 179 men (46.9%) and 203 women (53.1%). The t-test revealed statistically insignificant age and gender distribution (P = 0.59). Conclusion: The study found that dental patients at tertiary care were aware of the health issue, its potential spread, and preventive measures.